Workshop Pengembangan Lembar Kerja Interaktif dengan Liveworksheets untuk Guru Sekolah Dasar di Gugus 13 Kota Palangka Raya - Sion, Holten; Poerwadi, Petrus; Debora; Demitra; Misrita; Perdana, Indra; Silvianti, Annisa; Natasya (Jurnal Pengabdian Kampus, 2024)
The challenge elementary school teachers face in the digital era is that using platform facilities to support learning is not optimal. This workshop aims to provide (1) training in using Liveworksheets and (2) evaluating elementary school teachers' interest in developing worksheets with the Liveworksheets application. This community service activity is carried out in the planning, implementation, and reflection stages. Participants were 14 elementary school teachers in Cluster 13 Palangka Raya. The interest evaluation instrument uses the Liveworksheet Platform and questionnaire. Data were analyzed using descriptive analysis. The results of this workshop completing the workshop for making worksheets using Liveworksheet: (1) elementary school teachers' interest in Liveworksheets is in the high and very high range; (2) Liveworksheets are attractive because of the appearance they create in the application; (3) it is felt that the existence of the Liveworksheet has increased teachers' interest in making their worksheets; (4) teachers are interested in trying to make worksheets themselves with Liveworksheet; (5) teachers need Liveworksheets as a facility for creating worksheets. Based on the analysis of teachers' interest in using Liveworksheets, it can be concluded that providing technical guidance to make worksheets with Liveworksheets is interesting, needed, and motivates teachers to make worksheets for their learning.